Heart Transplantation in Adult Congenital Heart Disease with the Organ Care System Use: A 4-Year Single-Center Experience. Issue 8 (August 2021) - Verzelloni Sef, Alessandra; Sef, Davorin; Garcia Saez, Diana; Trkulja, Vladimir; Walker, Christopher; Mitchell, Jerry; McGovern, Ian; Stock, Ulrich
Abstract : Recent advances in the management of patients with adult congenital heart disease (ACHD) have led to an increased number of patients who may develop heart failure and require heart transplantation (HTx). The purpose of this study was to evaluate early and mid-term postoperative outcomes after HTx with the use of Organ Care System (OCS) in a cohort of ACHD patients transplanted at our tertiary center. All consecutive HTx performed from January 2015 to January 2019 at our institution were analyzed. Donor and recipient preoperative characteristics, intraoperative course, and perioperative clinical outcomes were evaluated. Nine patients with median age of 44 years (range 17–61 years) underwent isolated HTx for end-stage ACHD during the study period. Mean cold ischemic time was 84 ± 17 minutes. Postoperatively, four patients (44%) needed venoarterial extracorporeal membrane oxygenation (1–7 days). One patient (11%) required surgical re-exploration for bleeding. Thirty-day and 1-year mortality were 11% and 22%, respectively. In our experience, despite the challenges of transplantation in ACHD, these patients can be successfully transplanted with the use of the OCS in a highly specialized center. Careful donor and recipient selection are of paramount importance.